5.1.47 Problems 4601 to 4700

Table 5.93: First order ode

#

ODE

Mathematica

Maple

10380

\[ {}f \left (x^{c} y\right ) \left (b x y^{\prime }-a \right )-x^{a} y^{b} \left (x y^{\prime }+c y\right ) = 0 \]

10381

\[ {}{y^{\prime }}^{2}+a y+b \,x^{2} = 0 \]

10382

\[ {}{y^{\prime }}^{2}+y^{2}-a^{2} = 0 \]

10383

\[ {}{y^{\prime }}^{2}+y^{2}-f \left (x \right )^{2} = 0 \]

10384

\[ {}{y^{\prime }}^{2}-y^{3}+y^{2} = 0 \]

10385

\[ {}{y^{\prime }}^{2}-4 y^{3}+a y+b = 0 \]

10386

\[ {}{y^{\prime }}^{2}+a^{2} y^{2} \left (\ln \left (y\right )^{2}-1\right ) = 0 \]

10387

\[ {}{y^{\prime }}^{2}-2 y^{\prime }-y^{2} = 0 \]

10388

\[ {}{y^{\prime }}^{2}+a y^{\prime }+b x = 0 \]

10389

\[ {}{y^{\prime }}^{2}+a y^{\prime }+b y = 0 \]

10390

\[ {}{y^{\prime }}^{2}+\left (x -2\right ) y^{\prime }-y+1 = 0 \]

10391

\[ {}{y^{\prime }}^{2}+\left (x +a \right ) y^{\prime }-y = 0 \]

10392

\[ {}{y^{\prime }}^{2}-\left (1+x \right ) y^{\prime }+y = 0 \]

10393

\[ {}{y^{\prime }}^{2}+2 x y^{\prime }-y = 0 \]

10394

\[ {}{y^{\prime }}^{2}-2 x y^{\prime }+y = 0 \]

10395

\[ {}{y^{\prime }}^{2}+a x y^{\prime }-b \,x^{2}-c = 0 \]

10396

\[ {}{y^{\prime }}^{2}+a x y^{\prime }+b y+c \,x^{2} = 0 \]

10397

\[ {}{y^{\prime }}^{2}+\left (a x +b \right ) y^{\prime }-a y+c = 0 \]

10398

\[ {}{y^{\prime }}^{2}-2 x^{2} y^{\prime }+2 x y = 0 \]

10399

\[ {}{y^{\prime }}^{2}+a \,x^{3} y^{\prime }-2 a \,x^{2} y = 0 \]

10400

\[ {}{y^{\prime }}^{2}+\left (y^{\prime }-y\right ) {\mathrm e}^{x} = 0 \]

10401

\[ {}{y^{\prime }}^{2}-2 y y^{\prime }-2 x = 0 \]

10402

\[ {}{y^{\prime }}^{2}-\left (1+4 y\right ) y^{\prime }+\left (1+4 y\right ) y = 0 \]

10403

\[ {}{y^{\prime }}^{2}+a y y^{\prime }-b x -c = 0 \]

10404

\[ {}{y^{\prime }}^{2}+\left (b x +a y\right ) y^{\prime }+a b x y = 0 \]

10405

\[ {}{y^{\prime }}^{2}-x y y^{\prime }+y^{2} \ln \left (a y\right ) = 0 \]

10406

\[ {}{y^{\prime }}^{2}+2 y y^{\prime } \cot \left (x \right )-y^{2} = 0 \]

10407

\[ {}{y^{\prime }}^{2}+2 f \left (x \right ) y y^{\prime }+g \left (x \right ) y^{2}+h \left (x \right ) = 0 \]

10408

\[ {}{y^{\prime }}^{2}+y \left (y-x \right ) y^{\prime }-x y^{3} = 0 \]

10409

\[ {}{y^{\prime }}^{2}-2 x^{3} y^{2} y^{\prime }-4 x^{2} y^{3} = 0 \]

10410

\[ {}{y^{\prime }}^{2}-3 x y^{{2}/{3}} y^{\prime }+9 y^{{5}/{3}} = 0 \]

10411

\[ {}2 {y^{\prime }}^{2}+\left (x -1\right ) y^{\prime }-y = 0 \]

10412

\[ {}2 {y^{\prime }}^{2}-2 x^{2} y^{\prime }+3 x y = 0 \]

10413

\[ {}3 {y^{\prime }}^{2}-2 x y^{\prime }+y = 0 \]

10414

\[ {}3 {y^{\prime }}^{2}+4 x y^{\prime }-y+x^{2} = 0 \]

10415

\[ {}a {y^{\prime }}^{2}+b y^{\prime }-y = 0 \]

10416

\[ {}a {y^{\prime }}^{2}+b \,x^{2} y^{\prime }+c x y = 0 \]

10417

\[ {}a {y^{\prime }}^{2}+y y^{\prime }-x = 0 \]

10418

\[ {}a {y^{\prime }}^{2}-y y^{\prime }-x = 0 \]

10419

\[ {}x {y^{\prime }}^{2}-y = 0 \]

10420

\[ {}x {y^{\prime }}^{2}-2 y+x = 0 \]

10421

\[ {}x {y^{\prime }}^{2}-2 y^{\prime }-y = 0 \]

10422

\[ {}x {y^{\prime }}^{2}+4 y^{\prime }-2 y = 0 \]

10423

\[ {}x {y^{\prime }}^{2}+x y^{\prime }-y = 0 \]

10424

\[ {}x {y^{\prime }}^{2}+y y^{\prime }+a = 0 \]

10425

\[ {}x {y^{\prime }}^{2}+y y^{\prime }-x^{2} = 0 \]

10426

\[ {}x {y^{\prime }}^{2}+y y^{\prime }+x^{3} = 0 \]

10427

\[ {}x {y^{\prime }}^{2}+y y^{\prime }-y^{4} = 0 \]

10428

\[ {}x {y^{\prime }}^{2}+\left (-3 x +y\right ) y^{\prime }+y = 0 \]

10429

\[ {}x {y^{\prime }}^{2}-y y^{\prime }+a = 0 \]

10430

\[ {}x {y^{\prime }}^{2}-y y^{\prime }+a y = 0 \]

10431

\[ {}x {y^{\prime }}^{2}+2 y y^{\prime }-x = 0 \]

10432

\[ {}x {y^{\prime }}^{2}-2 y y^{\prime }+a = 0 \]

10433

\[ {}x {y^{\prime }}^{2}-2 y y^{\prime }-x = 0 \]

10434

\[ {}x {y^{\prime }}^{2}-2 y y^{\prime }+4 x = 0 \]

10435

\[ {}x {y^{\prime }}^{2}-2 y y^{\prime }+2 y+x = 0 \]

10436

\[ {}x {y^{\prime }}^{2}+a y y^{\prime }+b x = 0 \]

10437

\[ {}\left (1+x \right ) {y^{\prime }}^{2}-\left (x +y\right ) y^{\prime }+y = 0 \]

10438

\[ {}\left (1+3 x \right ) {y^{\prime }}^{2}-3 \left (y+2\right ) y^{\prime }+9 = 0 \]

10439

\[ {}\left (3 x +5\right ) {y^{\prime }}^{2}-\left (3 y+x \right ) y^{\prime }+y = 0 \]

10440

\[ {}a x {y^{\prime }}^{2}+\left (b x -a y+c \right ) y^{\prime }-b y = 0 \]

10441

\[ {}a x {y^{\prime }}^{2}-\left (a y+b x -a -b \right ) y^{\prime }+b y = 0 \]

10442

\[ {}\left (\operatorname {a2} x +\operatorname {c2} \right ) {y^{\prime }}^{2}+\left (\operatorname {a1} x +\operatorname {b1} y+\operatorname {c1} \right ) y^{\prime }+\operatorname {a0} x +\operatorname {b0} y+\operatorname {c0} = 0 \]

10443

\[ {}x^{2} {y^{\prime }}^{2}-y^{4}+y^{2} = 0 \]

10444

\[ {}\left (x y^{\prime }+a \right )^{2}-2 a y+x^{2} = 0 \]

10445

\[ {}\left (x y^{\prime }+y+2 x \right )^{2}-4 x y-4 x^{2}-4 a = 0 \]

10446

\[ {}y^{\prime }-1 = 0 \]

10447

\[ {}x^{2} {y^{\prime }}^{2}-2 x y y^{\prime }+y \left (1+y\right )-x = 0 \]

10448

\[ {}x^{2} {y^{\prime }}^{2}-2 x y y^{\prime }+y^{2} \left (-x^{2}+1\right )-x^{4} = 0 \]

10449

\[ {}x^{2} {y^{\prime }}^{2}-\left (2 x y+a \right ) y^{\prime }+y^{2} = 0 \]

10450

\[ {}x^{2} {y^{\prime }}^{2}+3 x y y^{\prime }+2 y^{2} = 0 \]

10451

\[ {}x^{2} {y^{\prime }}^{2}+3 x y y^{\prime }+3 y^{2} = 0 \]

10452

\[ {}x^{2} {y^{\prime }}^{2}+4 x y y^{\prime }-5 y^{2} = 0 \]

10453

\[ {}x^{2} {y^{\prime }}^{2}-4 x \left (y+2\right ) y^{\prime }+4 y \left (y+2\right ) = 0 \]

10454

\[ {}x^{2} {y^{\prime }}^{2}+\left (x^{3}+x^{2} y-2 x y\right ) y^{\prime }+\left (y^{2}-x^{2} y\right ) \left (1-x \right ) = 0 \]

10455

\[ {}x^{2} {y^{\prime }}^{2}-y \left (y-2 x \right ) y^{\prime }+y^{2} = 0 \]

10456

\[ {}x^{2} {y^{\prime }}^{2}+\left (a \,x^{2} y^{3}+b \right ) y^{\prime }+a b y^{3} = 0 \]

10457

\[ {}\left (x^{2}+1\right ) {y^{\prime }}^{2}-2 x y y^{\prime }+y^{2}-1 = 0 \]

10458

\[ {}\left (x^{2}-1\right ) {y^{\prime }}^{2}-1 = 0 \]

10459

\[ {}\left (x^{2}-1\right ) {y^{\prime }}^{2}-y^{2}+1 = 0 \]

10460

\[ {}\left (-a^{2}+x^{2}\right ) {y^{\prime }}^{2}+2 x y y^{\prime }+y^{2} = 0 \]

10461

\[ {}\left (-a^{2}+x^{2}\right ) {y^{\prime }}^{2}-2 x y y^{\prime }-x^{2} = 0 \]

10462

\[ {}\left (x^{2}+a \right ) {y^{\prime }}^{2}-2 x y y^{\prime }+y^{2}+b = 0 \]

10463

\[ {}\left (2 x^{2}+1\right ) {y^{\prime }}^{2}+\left (y^{2}+2 x y+x^{2}+2\right ) y^{\prime }+2 y^{2}+1 = 0 \]

10464

\[ {}\left (a^{2}-1\right ) x^{2} {y^{\prime }}^{2}+2 x y y^{\prime }-y^{2}+a^{2} x^{2} = 0 \]

10465

\[ {}a \,x^{2} {y^{\prime }}^{2}-2 a x y y^{\prime }+y^{2}-a \left (a -1\right ) x^{2} = 0 \]

10466

\[ {}x^{3} {y^{\prime }}^{2}+x^{2} y y^{\prime }+a = 0 \]

10467

\[ {}x \left (x^{2}-1\right ) {y^{\prime }}^{2}+2 \left (-x^{2}+1\right ) y y^{\prime }+x y^{2}-x = 0 \]

10468

\[ {}x^{4} {y^{\prime }}^{2}-x y^{\prime }-y = 0 \]

10469

\[ {}x^{2} \left (-a^{2}+x^{2}\right ) {y^{\prime }}^{2}-1 = 0 \]

10470

\[ {}{\mathrm e}^{-2 x} {y^{\prime }}^{2}-\left (y^{\prime }-1\right )^{2}+{\mathrm e}^{-2 y} = 0 \]

10471

\[ {}\left ({y^{\prime }}^{2}+y^{2}\right ) \cos \left (x \right )^{4}-a^{2} = 0 \]

10472

\[ {}\operatorname {d0} \left (x \right ) {y^{\prime }}^{2}+2 \operatorname {b0} \left (x \right ) y y^{\prime }+\operatorname {c0} \left (x \right ) y^{2}+2 \operatorname {d0} \left (x \right ) y^{\prime }+2 \operatorname {e0} \left (x \right ) y+\operatorname {f0} \left (x \right ) = 0 \]

10473

\[ {}y {y^{\prime }}^{2}-1 = 0 \]

10474

\[ {}y {y^{\prime }}^{2}-{\mathrm e}^{2 x} = 0 \]

10475

\[ {}y {y^{\prime }}^{2}+2 x y^{\prime }-y = 0 \]

10476

\[ {}y {y^{\prime }}^{2}+2 x y^{\prime }-9 y = 0 \]

10477

\[ {}y {y^{\prime }}^{2}-2 x y^{\prime }+y = 0 \]

10478

\[ {}y {y^{\prime }}^{2}-4 x y^{\prime }+y = 0 \]

10479

\[ {}y {y^{\prime }}^{2}-4 a^{2} x y^{\prime }+a^{2} y = 0 \]